Increased stability of a subtropic bamboo forest soil bacterial communities through integration of water and fertilizer management compared to conventional management - Yi Li; Zacchaeus G. Compson; Xiaobao Kuang; Lin Yu; Qingni Song; Jun Liu; Dongmei Huang; Hanchang Zhou; Siyuan Huang; Ting Li; Qingpei Yang (BMC Plant Biology)
Abstract Background Conventional management (CM), substantial fertilization and flooding irrigation, has led to soil acidification, the decrease in soil bacterial diversity in bamboo forests. Integration of water and fertilizer management (IWF) can effectively improve the efficiency of water and fertilizer use, but its effect on soil environment, especially on microbial community, is still unclear. Methods Here, we used next-generation high-throughput sequencing to compare soil properties and bacterial communities through different fertilization and irrigation methods under IWF and CM. Results Compared to the control group, CM significantly reduced soil pH and bacterial diversity, while IWF improved soil nutrition status, increased soil bacterial diversity and soil pH to a level similar to the control group. Compared with CM, IWF also improved the relative abundance of beneficial bacteria and copiotrophic bacteria community in the soil, and the bacterial community in IWF was similar to CK. The structure of the bacterial community was also significantly correlated with soil organic matter, total nitrogen, hydrolyzable nitrogen, and available potassium, while soil bacterial diversity was mainly associated with soil hydrolyzable nitrogen. Conclusions IWF can play an important role in preventing soil acidification, the loss of soil bacterial diversity, and improving the structure of the bacterial community under specific conditions.